(untitled) (Research, Society and Development, 2020)
The objective of this study was to evaluate the quality of eggs packaged in different types of packaging and stored at marketing stations in the municipality of São João del-Rei, over 35 days. 360 white eggs from Hy Line W36 liners were used, distributed in a completely randomized experimental design in a 2x3x5 factorial scheme (two storage locations / supermarkets (S1 and S2), 3 types of packaging (Styrofoam (Iso), plastic (Plas ) and cellulose (Cel)) and five evaluation periods: 7, 14, 21, 28 and 35 days), totaling 30 treatments with four repetitions, consisting of 3 eggs each. The data obtained for each parameter were subjected to analysis of variance, adopting a significance level of 5%. In case of statistical significance (P <0.05) for interaction between the period, type of packaging and supermarket, linear or quadratic regression models were adjusted for the response variables. Weight loss, albumen height, average albumen diameter and Haugh unit showed interaction (p <0.05) between Period, Supermarket and Packaging. Specific gravity decreased (p <0.05) after the 21st day of storage. The yolk and albumen pH and shell rate were not affected (p> 0.05) by the type of packaging. The eggs evaluated at 35 days showed high pH and yolk rate (p <0.05) and reduced pH and albumen rate (p <0.05). The storage period negatively affects the internal quality characteristics of the eggs. The plastic and Styrofoam packaging have better results in maintaining the quality of eggs over time, the first being more suitable. The location where the eggs are stored influences the quality of the egg. There was a difference between supermarkets.